Desulfurization of High‐Sulfur HIsarna Hot Metal. Issue 8 (21st December 2021) - Schrama, Frank N. H.; Beunder, Elisabeth M.; Emami, Ali; Barnes, Chris M.; van Boggelen, Johan W. K.; Sietsma, Jilt; Boom, Rob; Yang, Yongxiang
Abstract : The HIsarna process is one of the emerging low‐CO2 ironmaking processes that could help the steel industry in achieving their carbon footprint goals. HIsarna hot metal contains 3–4 times more sulfur than hot metal from blast furnaces (BFs). Therefore, a literature study, a thermodynamic analysis, and plant data analysis from Tata Steel, IJmuiden, are used herein to investigate the consequences of HIsarna hot metal for the current hot metal desulfurization process. Although the high sulfur concentration and low temperature of HIsarna hot metal lead to a higher total reagent consumption, compared with desulfurization of BF hot metal, the specific magnesium consumption decreases. The higher oxygen concentration in HIsarna hot metal only leads to a small increase in reagent consumption. Abstract : The HIsarna process, a low‐CO2 ironmaking process which currently is in the pilot phase, produces hot metal with 3–4 times more sulfur than a typical blast furnace. Herein, the effect of HIsarna hot metal on the hot metal desulfurization process is investigated with a literature study, a thermodynamic analysis, and plant data analysis.